Examining financial problems faced by university students - Mohamad Fahmy Amry Mohamad Noh (2012)
The purpose of this study was to explore how students manage their financial and the factors of financial problem. This study was designed to gain a better understanding of the financial problem of university students. A stratified purposeful sample of 220 students was selected for study. The data were analyzed for two purposes. The first purpose was to understand where participants spent their money, on what kinds of items, and their sources of income. This information was collected through a quantitative analysis of documents. The second purpose was to understand how and why the participants made the financial decisions they did during the period under study, and to gain an understanding of their larger financial situations. This information was collected through a quantitative analysis of distribute questionnaire. Results revealed several important findings. First, spending patterns can be traced to developmental issues associated with lower division students. For example, freshmen spend more money on food and entertainment than their sophomore counterparts, suggesting that social adjustment and making friends are important issues for first year students. Second, students from families which discuss financial issues have better money management skills. Third, students do not discuss financial matters outside their families, even with close friends. Coupled with the study’s other findings, these results suggest campuses need to provide programs and services related to financial management skills if students are to develop sound personal budgeting skills while in university